2015
DOI: 10.1007/s10598-015-9283-0
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm for a Positive Solution of Arbitrary Fully Fuzzy Linear System

Abstract: This paper proposes a new computational method to obtain a positive solution for arbitrary fully fuzzy linear system (FFLS). The new method transforms the coefficients in FFLS to a one-block matrix. As a result, none of the fuzzy operations are needed. This method can provide a solution regardless of the size of a system. Some necessary theorems are proved and new numerical examples are presented to illustrate the proposed method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This is because a near-zero fuzzy number cannot be defined in the form of (m, α, β), unlike a positive or negative fuzzy number could. Therefore, a new form of multiplication arithmetic operator has been introduced by [24] which adapted the system of min-max function.…”
Section: Triangular Fuzzy Number Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because a near-zero fuzzy number cannot be defined in the form of (m, α, β), unlike a positive or negative fuzzy number could. Therefore, a new form of multiplication arithmetic operator has been introduced by [24] which adapted the system of min-max function.…”
Section: Triangular Fuzzy Number Definitionmentioning
confidence: 99%
“…Theorem 1. [24] Consider an arbitrary fuzzy numberM = (m, α, β) and a positive fuzzy number N = (n, γ, δ), i. IfM is positive, then the following inequalities are satisfied:…”
Section: Definitionmentioning
confidence: 99%
“…Theorem 1 [24] Consider an arbitrary fuzzy numberM = (m a , α a , β a ) and positive fuzzy solutionX = (m x , α x , β x ) .…”
Section: Preliminariesmentioning
confidence: 99%
“…There are many authors have written about developing fuzzy analysis, significantly solving fully fuzzy linear and nonlinear systems. Different methods have been used to solve these two types of fully fuzzy systems, including a method for computing the positive solution of a fully fuzzy linear system (Ezzati et al, 2012); a method used to solve a fully fuzzy linear system via decomposing the symmetric coefficient matrix into two equations systems with the Cholesky method (Senthilkumar and Rajendran, 2011); the Jacobi iteration method for solving a fully fuzzy linear system with fuzzy arithmetic (Marzuki, 2015) and triangular fuzzy number (Megarani et al, 2022); a method for finding a positive solution for an arbitrary fully fuzzy linear system with a one-block matrix (Malkawi et al, 2015a); the singular value decomposition method for solving a fully fuzzy linear system (Marzuki et al, 2018); the Gauss-Seidel method for solving a fully fuzzy linear system via alternative multi-playing triangular fuzzy numbers (Deswita and Mashadi, 2019); the Jacobi, Gauss-Seidel, and SOR iterative methods for solving linear fuzzy systems (Inearat and Qatanani, 2018);a linear programming approach utilizing equality constraints to find non-negative fuzzy numbers (Otadi and Mosleh, 2012); combining interval arithmetic with trapezoidal fuzzy numbers to solve a fully fuzzy linear system (Siahlooei and Fazeli, 2018); using an ST decomposition with trapezoidal fuzzy numbers to solve dual fully fuzzy linear systems via alternative fuzzy algebra (Safitri and Mashadi, 2019), using LU factorizations of coefficient matrices for trapezoidal fuzzy numbers to solve dual fully fuzzy linear systems (Marni et al, 2018); combining QR decomposition with trapezoidal fuzzy numbers (Gemawati et al, 2018); and using an ST decomposition with trapezoidal fuzzy numbers to solve a dual fully fuzzy linear system (Jafarian, 2016). In the case of fully fuzzy linear matrix equations, several studies have identified methods for solving them, including a method that utilizes fully fuzzy Sylvester matrix equations (Daud et al, 2018;Elsayed et al, 2022;He et al, 2018;Malkawi et al, 2015b), and a method that finds fuzzy approximate solutions (Guo and Shang, 2013).…”
Section: Introductionmentioning
confidence: 99%